Cross-curricular collaboration in a CLIL bilingual context: the perceptions and practices of language teachers and content subject teachers - Pham, Phuong Anh; Unaldi, Aylin (International journal of bilingual education and bilingualism, 2022)
Content and Language integrated learning (CLIL) revolves around the dual goal of language acquisition and content knowledge; therefore, the cross-curricular collaboration between language and content teachers is one of the key factors for the success of CLIL education. This study investigates multiple aspects of cross-curricular collaboration in a Vietnamese CLIL program, including teachers' beliefs about pedagogic roles, professional support provided, and actual cross-curricular collaboration implemented. Data collected from eight teachers through semi-structured interviews were coded for emerging themes using thematic analysis, and relevant documents were analysed as complementary data. The findings indicate that the teachers viewed their pedagogical responsibilities and foci rigidly within their discipline, rather than as a dual-focused role of both language and content teaching. Additionally, a mismatch between professional support provided by the school and by the program designers was identified, indicating insufficient training and supervision in the implementation of the program. Although there was evidence of teacher collaboration, the practice still lacked consistency and systematicity due to issues such as workload, schedule and motivation. The findings from this study have important implications for professional development and curriculum design in CLIL bilingual programs to facilitate successful cross-curricular collaboration.